First‐in‐human study of ONO‐4578, an antagonist of prostaglandin E2 receptor 4, alone and with nivolumab in solid tumors. Issue 1 (4th November 2022) - Iwasa, Satoru; Koyama, Takafumi; Nishino, Makoto; Kondo, Shunsuke; Sudo, Kazuki; Yonemori, Kan; Yoshida, Tatsuya; Tamura, Kenji; Shimizu, Toshio; Fujiwara, Yutaka; Kitano, Shigehisa; Shimomura, Akihiko; et al.
Abstract: EP4, a prostaglandin E2 receptor, has shown an immunosuppressive activity on cancer cells. This first‐in‐human study evaluated ONO‐4578, a highly selective EP4 antagonist, as monotherapy and in combination with nivolumab in patients with advanced or metastatic solid tumors. A daily dose ranging from 30 mg to 100 mg of ONO‐4578 monotherapy and that ranging from 2 mg to 60 mg of ONO‐4578 with biweekly nivolumab 240 mg were administered. A total of 31 patients were enrolled, 10 receiving monotherapy and 21 receiving combination therapy. Overall, 26 patients experienced treatment‐related adverse events. Dose‐limiting toxicities were observed in three patients; one of six patients receiving 100 mg monotherapy developed grade 3 duodenal ulcer and two of six patients receiving 60 mg combination therapy developed either grade 3 erythema multiforme or grade 3 increased amylase and grade 4 increased lipase. One patient with small‐cell lung cancer who received 40 mg combination therapy had a partial response, and three patients with monotherapy and six patients with combination therapy had stable disease. Pharmacodynamics analyses showed that ONO‐4578 had EP4 antagonistic activity at doses as low as 2 mg. In conclusion, the maximum tolerated dose of ONO‐4578 alone or in combination with nivolumab was not reached. ONO‐4578 was well tolerated at the tested doses and showed signs of antitumor activity. Considering safety, efficacy, and pharmacokinetics/pharmacodynamics results, ONO‐4578 40 mg daily with nivolumab 240 mg biweekly was selected as the recommended dose for future clinical trials. (Registration: JapicCTI‐173, 496 and NCT03155061). Abstract : ONO‐4578 is a selective antagonist of the EP4 receptor for prostaglandin E 2 . ONO‐4578 alone or in combination with nivolumab was well tolerated and showed signs of anti‐tumor activity in patients with advanced or metastatic solid tumors. Considering safety, efficacy, and pharmacokinetics/pharmacodynamics results, ONO‐4578 40 mg daily with nivolumab 240 mg biweekly was selected as the recommended dose for future clinical trials.